Allelopathic research in Brazil - Reigosa,Manuel (2013)
In this article, we review allelopathy studies conducted in Brazil or involving plant species that occur in the country. Conceptions and misconceptions associated with allelopathy, as well as some international criteria to be applied in allelopathic research, are presented and discussed. We observed a sharp increase in the number of papers on this subject conducted in Brazil between 1991 and 2010. However, most studies are conducted under laboratory conditions, lack a clear hypothesis or a solid justification, and typically make use of target species that do not co-exist with the donor species under natural conditions. We also found that most studies do not take the additional steps in order to purify and identify the bioactive molecules. We recommend that further studies be conducted in order to explore the potential of plant biodiversity in Brazil. Such studies could lead to the development of new molecular structures (allelochemicals) that could be used in the control of pests and weeds, thereby reducing the use of the harmful synthetic herbicides that are currently being widely employed.